2007
DOI: 10.1111/j.1600-079x.2007.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin influences the proliferative and differentiative activity of neural stem cells

Abstract: Though melatonin has a wide variety of biological functions, its effects on the neural stem cells (NSCs) is still unknown. In this study, we examined the effects of melatonin at either physiological (0.01-10 nm) or pharmacological concentrations (1-100 microM) on the proliferation and neural and astroglial differentiation of NSCs derived from the mouse embryo striatum using an in vitro culture system. We found that melatonin at pharmacological concentrations, but not at physiological concentrations, suppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
99
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 45 publications
12
99
2
3
Order By: Relevance
“…More recently it has been reported that exogenous melatonin could increase the survival of neuronal progenitor cells and postmitotic immature neurons in the hippocampus of adult mice (Ramírez-Rodríguez et al, 2009), consistent with melatonin actions on proliferative activity in the rat dentate gyrus and embryonic neural stem cells (Kim et al, 2004;Moriya et al, 2007). These findings are particularly interesting in view of the recent reports that melatonin can reduce learning and memory deficits in mice models of Alzheimer disease (Feng et al, 2004;Olcese et al, 2009).…”
Section: B Melatonin Receptor Functionsupporting
confidence: 55%
“…More recently it has been reported that exogenous melatonin could increase the survival of neuronal progenitor cells and postmitotic immature neurons in the hippocampus of adult mice (Ramírez-Rodríguez et al, 2009), consistent with melatonin actions on proliferative activity in the rat dentate gyrus and embryonic neural stem cells (Kim et al, 2004;Moriya et al, 2007). These findings are particularly interesting in view of the recent reports that melatonin can reduce learning and memory deficits in mice models of Alzheimer disease (Feng et al, 2004;Olcese et al, 2009).…”
Section: B Melatonin Receptor Functionsupporting
confidence: 55%
“…High concentrations of melatonin in an exposure-timing-dependent manner (104) and at physiologic concentration, particularly through MT 1 receptors in the SVZ, have a modulatory effect on neural stem cell proliferation and differentiation (86). Recent studies have identified functions in neurogenesis for MT 1 and MT 2 agonists, including agomelatine (105,106), buspirone in combination with melatonin in major depressive disorder (107), and Nacetylserotonin, an intermediate of melatonin synthesis (108).…”
Section: Central and Peripheral Nscs Agingmentioning
confidence: 99%
“…Крім того, встановлено його позитивний вплив на порушений функціональний стан тимуса, баланс регуляторних субпопуляцій Т-лімфо-цитів і активність макрофагів [25,26]. Є дані щодо підсилення під впливом мелатоніну проліферативного потенціалу НСК головно-го мозку та їх диференціювання у напрямку нейронів [22,27,28].…”
Section: вступunclassified
“…Ми припустили, що застосування при паркінсонізмі фармакологічних засобів, які спроможні одночасно вплинути на актив-ність факторів імунної системи та анти-оксидантного захисту, може спричинити і нейропротекторний ефект. Так, за даними літератури, позитивний вплив мелатоніну на етапи нейрогенезу у головному мозку пов'язаний не тільки з комбінацією анти-оксидантного і антиапоптотичного ефек-тів, але й посиленням проліферативного потенціалу НСК та їх диференціювання у нейрони, зміною активності та/або вмісту деяких факторів мікрооточення (зокрема, BDNF, нейротрофічний фактор головного мозку), які важливі для виживання нейраль-них клітин та утворення нових нейронів [22,27]. Дійсно, нами встановлено, що курсове введення мелатоніну підтримує підвищений вміст НСК у нюховій цибулині дослідних щурів без рухової асиметрії.…”
Section: результати та їх обговоренняunclassified